Implications of Intellectual Capital Financial Performance and Corporate Values (Studies on Goods and Consumption Sector 2013-2017 period) - Susanti, Neneng (International Journal of Psychosocial Rehabilitation, 2020)
This research is conducted considering that intellectual capital is an important resource that is used to create added value for companies in the era of knowledge-based business. This research was conducted in the goods and consumption sector in the period 2013-2017 Because The goods and consumption sector companies had the highest investment rates Compared to other industrial sectors. The purpose of this study was to Determine the effect of intellectual capital on firm value, the effect of intellectual capital on financial performance, and the effect of financial performance on firm value. This type of research is an explanatory study with a quantitative approach, using the Partial Least Square (PLS) method with a Smart PLS 3.0 application. The results of this study indicate that there is no significant positive effect between intellectual capital and firm value. In addition, this study shows that intellectual capital has a significant effect on financial performance, and financial performance has an effect on firm value. This study shows that the value of companies in the goods and consumption sector is influenced by intellectual capital.